1994
DOI: 10.1063/1.468107
|View full text |Cite
|
Sign up to set email alerts
|

Threshold for quasicontinuum absorption and reduced luminescence efficiency in CdSe nanocrystals

Abstract: Luminescence excitation spectra are employed to study the electronic states of CdSe nanocrystals ranging in size from 9 to 26 Å radius at 77 K. These studies show that all samples have, in addition to the discrete manifold of quantum confined electronic excitations, a threshold for continuum absorption. Absorption into this continuum results in substantially reduced luminescence efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
136
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(157 citation statements)
references
References 18 publications
21
136
0
Order By: Relevance
“…We observed an anomalous dependence of quantum yields on the excitation wavelengths especially at wavelengths shorter than 420nm. This behavior is consistent with published literature on dots (16,17). Photo excitation of QD585 in the wavelength window between 420 and 500 nm yielded, on average, a uniform quantum efficiency of ≈ 0.20.…”
Section: Introductionsupporting
confidence: 91%
“…We observed an anomalous dependence of quantum yields on the excitation wavelengths especially at wavelengths shorter than 420nm. This behavior is consistent with published literature on dots (16,17). Photo excitation of QD585 in the wavelength window between 420 and 500 nm yielded, on average, a uniform quantum efficiency of ≈ 0.20.…”
Section: Introductionsupporting
confidence: 91%
“…The emission yield of the QD525 dots also significantly drops to 15% at 350 nm from a high of 40% at 450 nm. The level of drop (≤50%) in quantum yield at the high-energy end for both samples is consistent with literature reports (16,52). The difference in behavior between the QD525 and QD585 dots appears to originate more from differences in size distribution rather than intrinsic properties where the smaller QD525 dots appear to be more heterogeneous (c.f.…”
Section: On the Correspondence Of Absorption And Photoexcitation Specsupporting
confidence: 79%
“…Experimental data have shown a strong correlation between the method of dot preparation and excited state behavior (23). Several authors reported a decrease of emission yield with decreasing wavelength, suggesting an anomalous dependence of excitation on wavelength (24,25,37,38,52). Potential mechanisms for this process have been postulated, including the hypothesized existence of electronic relaxation channels of "hot" electrons, which bypass the lowest excited state (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the range of size of QDs in that work was 2-8 nm. In that and other works [3][4][5][6], authors assure that except excitonic peaks there is a wide luminescence band which is caused by the impurity and surface states.…”
Section: Introductionmentioning
confidence: 99%